PERSUASION IN EMMA WATSON’S SPEECH AT ONE YOUNG WORLD A CRITICAL DISCOURSE ANALYSIS - Christina , Sarah; Pradipta, Bramantya (TANDA, 2022)
The purpose of the study is to analyze persuasive element and ideology contained in Emma Watson’s speech at One Young World (2016). Theory of Fairclough about persuasion in speech was applied in order to get the result. The study used Fairclough’s theory which consists of three stages; the description level, the interpretation level, and the explanation level. The result of the analysis discovered that Emma Watson’s speech contained persuasion through vocabulary, figurative language, grammatical process, passivization, modality, pronouns, reported speech, and repetition. In addition, the ideologies behind her speech are the ideology of unity, gender equality, and feminism.